Identifying key determinants of housing sales and time-on-the-market (TOM) using fuzzy cognitive mapping - Ferreira , Fernando A. F.; Jalali, Marjan S. (International Journal of Strategic Property Management, 2015)
Price and residential housing attributes have long been identified as key determinants of home sales and, as such, they can explain time-on-the-market (TOM). It is acknowledged, however, that there are other factors (or determinants) that influence home sales and TOM, which are of great importance but seldom taken into account in the appraisal process of residential real estate. Based on the use of fuzzy cognitive mapping, we propose a framework that adds value to the way that key determinants of housing sales and TOM are identified. This framework is the result of a process involving several residential real estate experts (i.e.appraisers and realtors), and follows a constructivist approach. Our findings suggest that the use of fuzzy cognitive maps (FCMs) allows the number of omitted determinants to be reduced and the understanding of the relationships between them to be improved. The strengths and weaknesses of our methodological framework are also discussed. First Publish Online: 9 Oct 2015